Identifikasi Faktor Penyebab Kesulitan Belajar Siswa Kelas VIII di SMP PGRI Cicalengka - Sopiah, Sopi; Siti Latipah; Dwi Rahmawati; Eneng Metin Nuraeni; Muhamad Uli Nuha (Journal of Teacher Training and Educational Research, 2024)
Learning difficulties are a problem that causes a student to not be able to follow the learning process as well as other students in general. The aim of this research is to find out more about the factors that cause learning difficulties in class VIII students at PGRI Cicalengka Middle School. The research method used is a qualitative descriptive research method. The data collection techniques used are observation or observations in the field, interviews and documentation. The results of the research show that the learning difficulties experienced by class VIII students at PGRI Cicalengka Middle School are caused by several causal factors: (1) students' lack of concentration in studying, (2) students' lack of ability to understand certain subject matter, such as science subjects, English, Mathematics, and Informatics, (3) lack of teacher innovation in developing their teaching abilities, and (4) lack of support from parents.